Antecedents and Outcomes of Digital Influencer Endorsement: An Exploratory Study - Rizki Baihaqi; Adi Setiawan (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2026)
This study aims to analyze the effect of Digital Influencer Attractiveness and Brand Congruence on Brand Attitude, Purchase, and Repurchase Intention by adopting the Stimulus-Organism-Response (S-O-R) framework. Using a quantitative approach with a cross-sectional design, data were collected from 55 social media users in Cirebon selected through accidental sampling technique and processed using Path Analysis. The results showed that Attractiveness and Brand Congruence have a positive and significant effect on Brand Attitude. In addition, Attractiveness and Brand Attitude proved to have a significant effect on Purchase, which then became the strongest driving factor for Repurchase Intention. These findings also indicate the important mediating role of Brand Attitude and Purchase, considering that the direct paths from Brand Congruence to Purchase and Attractiveness to Repurchase Intention were found to be insignificant. Overall, this study concludes that an influencer marketing strategy that optimizes visual attractiveness and brand congruence is highly effective in shaping positive consumer attitudes, solidifying purchases, and driving repurchase intentions.